Dugandia, a new snake genus for coluber bicinctus herrmann (1944)
The snake species Coluber bicinctus Herrmann (1804, Obs. Zool. p. 276) has not previously been recorded from Colombia. A female measuring 785 mm., tail 195,was collected by my friend Paul H. Allen on Nov. 10, 1943, at Yurupari Falls, Vaupés River, Vaupés. It is now in the collection of the Instituto de Ciencias Naturales. Herrmann's type was without locality, and Duméril and Bibron (Erp. Gen. 7, 1854, p. 716) first mentioned a definite locality, Surinam, whence they had material. It has since been given the range of the Guianas and Venezuela, so that its occurrence in Colombia was to have been expected.